A distributed dynamic authorisation method for Internet+ medical & healthcare data access based on consortium blockchain. Issue 12 (2nd December 2022) - Xu, Boyi; Xu, Li Da; Wang, Yuxiao; Cai, Hongming
ABSTRACT: Privacy protection to medical & healthcare data is one of the bottleneck problems in Internet information fusion. In order to balance data processing capability with privacy concerns, a distributed dynamic authorisation method based on blockchain is proposed to realise trustworthy data access. URLs (Universal Resource Locator) are included in the authorisation information to indicate the data access interface as well as separating patients' privacy data from blockchain to improve data process efficiency. The contents of smart contracts are demonstrated in a case study to validate the usability of the proposed authorisation method in medical data access between different hospitals.